Section organized by - Rosenmüller, Christoph; Costa Vigo, Luis Miguel (Anuario de Historia de América Latina, 2020)
Scholars have paid much attention to the concept of the empire. Some emphasize the changing nature of the Iberian empires, while others draw attention to their pervasive and enduring structures. The articles in this dossier argue from different perspectives that the crown gradually achieved change in its favor although in limited aspects. The Crown negotiated with local groups or corporations, nudging and rewarding loyal vassals, while also threatening and punishing recalcitrants. According to the authors, this process was underway in the late sixteenth century, well before the reforms of the eighteenth century. The dossier combines contributions from specialists located in Mexico, Colombia, Chile, Portugal, and the United States for a fresh look at the challenges of empire.